Plant blindness in high school students: Identification and alternative solutions of the problem - Soraya, Puan Helwa Rezha; Kusumastuti, Mimin Nurjhani; Solihat, Rini (Assimilation: Indonesian Journal of Biology Education, 2025)
This study was conducted to determine the level of plant blindness in three schools in West Java. This study was also conducted with the aim of looking at the differences in the level of plant blindness as well as the relationship between the tests and questionnaires given to students. As a follow-up, this study discusses alternative solutions to the problems that arise in the three schools. The population of this study was three schools in West Java, namely one school in Bandung City, West Bandung Regency, and Indramayu Regency. From the population, one class was taken using Convenience sampling technique. The research method used was descriptive cross-sectional method. The data that has been obtained is then processed using descriptive and inferential statistics to see the differences and relationships. The results showed a significant difference between the three schools. The results also showed a positive relationship between the test results and the plant awareness questionnaire. This shows that students who have high plant awareness have high knowledge as well. The alternative solution proposed in this study is the use of eDNA Metabarcoding research as a practicum to study biodiversity, considering that eDNA can identify plant species specifically and accurately.